Epigenetic modification of nucleic acids: from basic studies to medical applications. (29th March 2017) - Chen, Yuqi; Hong, Tingting; Wang, Shaoru; Mo, Jing; Tian, Tian; Zhou, Xiang
Abstract : This review focuses on the recent progresses in epigenetic modifications in DNA and RNA, including their epigenetic roles, detection methods and applications in clinical medicine. Abstract : The epigenetic modification of nucleic acids represents one of the most significant areas of study in the field of nucleic acids because it makes gene regulation more complex and heredity more complicated, thus indicating its profound impact on aspects of heredity, growth, and diseases. The recent characterization of epigenetic modifications of DNA and RNA using chemical labelling strategies has promoted the discovery of these modifications, and the newly developed single-base or single-cell resolution mapping strategies have enabled large-scale epigenetic studies in eukaryotes. Due to these technological breakthroughs, several new epigenetic marks have been discovered that have greatly extended the scope and impact of epigenetic modifications in nucleic acids over the past few years. Because epigenetics is reversible and susceptible to environmental factors, it could potentially be a promising direction for clinical medicine research. In this review, we have comprehensively discussed how these epigenetic marks are involved in disease, including the pathogenesis, prevention, diagnosis and treatment of disease. These findings have revealed that the epigenetic modification of nucleic acids has considerable significance in various areas from methodology to clinical medicine and even in biomedical applications.